Pre-trial arrest warrant - Gavrilă, Renata-Gabriela (Technium Social Sciences Journal, 2023)
Referring to the provisions of the Romanian Constitution, individual freedom and security of person appear to be inviolable, unless criminal proceedings have been initiated against the person. Crime is that state of affairs which brings a high degree of danger to society. It consists in committing criminal acts with guilt, punishable by a criminal fine and/or deprivation of liberty. Preventive measures have the role of helping in the criminal process by meeting or removing situations of danger that could prevent the court from finding out the truth, as well as restricting the freedom of persons who have committed crimes or about whom there is reasonable suspicion that they are going to commit an act provided by criminal law. The deprivation of liberty of individuals who have committed crimes is a necessary measure for their re-education and aims to prevent the commission of other criminal acts. Among preventive measures, the most serious form is pre-trial detention. This is one of the most severe custodial measures by which the accused is interrupted from performing certain actions that could hinder the criminal process or its purpose. Pre-trial detention may be implemented only after the substantive conditions of the pre-trial detention warrant have been cumulatively met. Therefore, the arrest is a procedural measure without which pre-trial detention could not be ordered. It is a procedural act of particular importance because it presents, concretely, the act(s) of which the accused is accused and through this prism the necessary measures are taken to charge the defendant. The arrest warrant is the main document that makes the difference in order to establish a person’s guilt.